Efektifitas Pursed Lip Breathing Exercise Dan Posisi Fowler Pada Pasien Asthma: Studi Kasus - Fitriawanda, Asfira Niken; Sutrisno, Resti Yulianti (Universitas Muhammadiyah Yogyakarta, 2023)
Asthma is a chronic inflammatory disorder causing hyperresponsiveness in the airways which refers to recurrent episodes such as dyspnea, coughing, wheezing and chest tightness that can affect all age groups. Symptoms that appear are related to the extent of inflammation so that they are reversible with or without treatment which can cause asthma sufferers to have more sensitive airways and a decrease in vital capacity in the lungs characterized by an increase in functional residuals and residual lung volume so that oxygen levels in the blood reduced which causes a decrease in oxygen saturation levels in asthmatic patients. This case study aims to determine the effectiveness of pursed lip breathing and Fowler's position adjustment in increasing the oxygen saturation of asthmatic patients. The method in this study used a case study in asthmatic patients by giving pursed lip breathing and Fowler's position (90°). Pursed lip breathingis a breathing exercise with a shorter inspiratory phase than the expiratory phase. Pursed lip breathing is performed by inhaling through the nose by counting one to three and then exhaling slowly through pursed lips as if blowing out a candle, counting one to seven, each time you inhale, give a 2 second pause to start over. The results of the intervention showed that giving pursed lip breathing and semi-Fowler's position was effective in increasing oxygen levels in the body marked by a significant increase in oxygen saturation, namely 96-100%. Exercises Pursed lip breathing and semi-Fowler's position can increase oxygen saturation and reduce shortness of breath in people with asthma. Keywords: asthma, pursed lip breathing, Fowler's position